2015
DOI: 10.1186/s12893-015-0082-5
|View full text |Cite
|
Sign up to set email alerts
|

Loss of neuromonitoring signal during bilateral thyroidectomy: no systematic change in operative strategy according to a survey of the French Association of Endocrine Surgeons (AFCE)

Abstract: BackgroundTotal thyroidectomy presents a risk of bilateral vocal cord paralysis, which can lead to compromised airway. Visual Recurrent Laryngeal Nerve (RLN) identification significantly decreases this risk of RLN lesion. Yet, an anatomically intact nerve is not always functional. Intraoperative neuromonitoring (IONM) allows to test in real time the function of the RLN. In case of loss of signal (LOS) on the first operated side, some authors recommend to stop the intervention. The purpose of this study was to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…There are only few studies supporting the decrease in RLN palsy (transient) when using IONM compared to visual recognition alone, while the sample, for permanent palsy, was small to achieve a statistically significant result despite the decreased trend that it has also shown (8,17). Other large national studies (i.e., Scandinavian) showed contradictory results on the subject (21,22). Therefore, it is not yet safe to come to a clear conclusion.…”
Section: Introductionmentioning
confidence: 96%
“…There are only few studies supporting the decrease in RLN palsy (transient) when using IONM compared to visual recognition alone, while the sample, for permanent palsy, was small to achieve a statistically significant result despite the decreased trend that it has also shown (8,17). Other large national studies (i.e., Scandinavian) showed contradictory results on the subject (21,22). Therefore, it is not yet safe to come to a clear conclusion.…”
Section: Introductionmentioning
confidence: 96%
“…An enquiry among German endocrine and thyroid surgeons revealed that over 85 per cent of the surgical departments surveyed would be willing to discontinue surgery in the event of initial loss of signal. In contrast, a recent survey among French endocrine surgeons reported that only a minority would be in favour of staging a total thyroidectomy.…”
Section: Discussionmentioning
confidence: 82%
“…The prompt relief of symptoms and the best alleviation obtained in case of endocrine ophthalmopathy are also worth to be counted among its advantages. Although lifelong thyroxine replacement treatment should be applied to patients following total thyroidectomy, the complication ratio seem to be almost equal with those seen in nontotal procedures (4,5). Furthemore, in case of repeat surgery for recurrent disease, especially when the operation is performed by an inexperienced surgeon, the complication rates reach up to 20-25 % (3).…”
Section: Discussionmentioning
confidence: 99%
“…Meticulous hemostasis can be achieved with harmonic sealing instrument, since improper hemostasis is known to increase the risk of RLNI (4). Despite the lack of evidence to support an advantage of IONM over the standard anatomic dissection of RLN, surgeons have adopted it in increasing ratios (5,11,12).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation